Sperm content of TXNDC8 reflects sperm chromatin structure, pregnancy establishment, and incidence of multiple births after ART. (2nd September 2020) - Ahlering, Peter; Sutovsky, Miriam; Gliedt, Douglas; Branson, Kellie; Miranda Vizuete, Antonio; Sutovsky, Peter
ABSTRACT: Male germline-specific thioredoxin domain containing 8 (TXNDC8; alias SPTRX3) accumulates indefective human spermatozoa. We assessed the efficiency of two-step semen purification inremoving spermatozoa carrying TXNDC8, and examined the relationship of TXNDC8 with theoutcomes of assisted reproductive therapy (ART), conventional semen parameters, and sperm DNA integrity in sperm chromatin structure assay (SCSA). Semen samples (n = 255) from 91 ART couples were screened in two independent trials, both including a two-step, gradient-and-swim-up separation procedure yielding A-samples (raw semen), B-samples (gradient separated), and C-samples (gradient-and-swim-up). The C-samples were used for intracytoplasmic sperm injection (ICSI) with morphologically selected spermatozoa (IMSSI). Percentage of TXNDC8-positive spermatozoaincreased progressively from A to B/C-samples in both trials. In the first trial (35 couples), the TXNDC8 correlated positively with sperm DNA fragmentation index (%DFI; r = 0.66) measured before separation, and negatively with sperm concentration (r = −0.57) and motility (r = −0.67), also taken before separation. The high DNA stainability index (%HDS) correlated with the percentage of spermatozoa lacking TXNDC8 (r = 0.68). Both SCSA and TXNDC8 parameters showed moderate correlations (r = 0.33–0.66) with blood serum levels of hCG on day 11 (Beta 1) and day13 (Beta 2) after oocyte retrieval. In the second trial (56 couples), fathers of multiplets had a significantly lower percentage of TXNDC8-positive spermatozoa in B-sample (gradient separationonly) compared to men who conceived a singleton pregnancy (p = 0.01) and those who produced no pregnancy (p = 0.02). Those multiplets' fathers also had a significantly higher sperm concentration while their SCSA parameters did not differ from others. It is concluded that theTXNDC8 levels correlate with SCSA and conventional raw semen parameters, and are predictive of pregnancy outcome and multiple births after ART. Two-step purification does not efficiently remove TXNDC8 carrying spermatozoa. Abbreviations: ART– assisted reproductive therapy; DFI- DNA fragmentation index; FC- flow cytometry (FC); hCG: human chorionic gonadotropin; HDS: high DNA stainability index; HEPES- (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid); HTF- human tubal fluid; ICSI- intracytoplasmic sperm injection; IgG- immunoglobulin G; IMSSI- ICSI with morphologically selected spermatozoa; IVF- in vitro fertilization; IU-: intrauterine insemination; NGS- normal goat serum; PBS- phosphate buffered saline; PVP- polyvinylpyrrolidone; SAB- spontaneous abortion; SCSA- sperm chromatin structure assay; SPTRX3- spermatid specific thioredoxin 3; SSS- synthetic serum substitute; TRITC- tetramethyl rhodamine isothiocyanate; TX-100- Triton X-100; TXNDC- thioredoxin domain-containing proteins; TXNDC8- thioredoxin domain containing 8; TUNEL- Terminal deoxynucleotidyl transferase dUTP nick end labeling